Oxidative stress state during pregnancy period - Hassan, Iman Salman; Laylani, Layla Abd-Al-Sattar Sadiq (Iraqi Journal of Science, 2021)
The present study was designed to find the relation between oxidative stress andpregnancy. The study used one hundred twenty volunteers (ninety pregnant womenand thirty non-pregnant women). Then pregnant women were divided to threesubgroups according to trimester (first trimester, second trimester and thirdtrimester). then, some oxidative stress factors (MDA, GSH, catalase and TAC) weremeasurement. Biochemical tests showed significant (P<0.05) increase inmalonedialdehyied (MDA) and significant (P<0.05) decrease in Glutathione (GSH),Catalase (CAT) and total antioxidant capacity (TAC) in pregnant women comparedwith non-pregnant women group. It was concluded from this study that thepregnancy led to increased oxidative stress and decreased the antioxidant factors.